Kawasaki disease complicated by peripheral artery thrombosis: a case report and literature review - Nanjun Zhang; Li Yu; Zhongxian Xiong; Yimin Hua; Hongyu Duan; Lina Qiao; Kaiyu Zhou; Chuan Wang (BMC, 2022)
Abstract Background Peripheral gangrene is rarely documented as a possible complication of Kawasaki disease (KD). There are many causes of peripheral gangrene, and the common cause is in situ thrombosis or embolism. Most cases are reported to have regrettable outcomes (amputation or necrotic shedding). Herein, we report the successful management of KD complicated by peripheral artery thrombosis in an older Chinese boy, and a review of all cases of peripheral gangrene in KD in the literature. Case presentation We found that most of the children with this complication were under 1 year old, had a heavy inflammatory response combined with the use of cortisol and immunoglobulin, and most children had coronary artery lesions. In addition, Peripheral gangrene mainly occurred in the subacute or chronic stage, and the prognosis is poor. Conclusions In the presence of high risk factors, we consider it is necessary to monitor coagulation function and administer prophylactic anticoagulation therapy. When peripheral artery thrombosis or embolism occur, heparin and prostaglandins can be used for treatment.